2012
DOI: 10.2478/v10172-012-0075-7
|View full text |Cite
|
Sign up to set email alerts
|

An influence of mechanical mixing and hot-pressing on properties of NiAl/Al2O3 composite

Abstract: Intermetallic phases of the Ni-Al type belong to the group of modern constructional materials which have numerous advantageous properties such as high melting temperature, low density, high resistance to high-temperature oxidation (to about 1200• C), high mechanical strength, high fatigue strength, and high tensile and compressive strength (also at elevated temperatures). Intermetallic compounds have however also drawbacks in that they are quite brittle at room temperature which makes their mechanical processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…Manufacturing processes and properties of intermetallic NiAl composites with ceramic reinforcements have been discussed in several papers, cf. [3][4][5][6][7][8][9][10][11][12] In most of the referred studies, hot pressing process was employed to obtain a full dense composite material. Composite properties depend on various manufacturing features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manufacturing processes and properties of intermetallic NiAl composites with ceramic reinforcements have been discussed in several papers, cf. [3][4][5][6][7][8][9][10][11][12] In most of the referred studies, hot pressing process was employed to obtain a full dense composite material. Composite properties depend on various manufacturing features.…”
Section: Introductionmentioning
confidence: 99%
“…[4] that the phase composition of NiAl/Al 2 O 3 composite has a crucial impact on the toughness enhancement. An influence of mechanical powder mixing on properties of NiAl/Al 2 O 3 composite was studied in Refs [3,6]. The experiments have shown that the physical and mechanical properties such as bulk density, strength and hardness of the composite closely depend on the parameters of both the mixing and sintering processes.…”
Section: Introductionmentioning
confidence: 99%
“…Another method for hardening a two-phase NiAl/Ni 3 Al matrix consists in the introduction of fine ceramic particles uniformly distributed therein. Beneficial effects of this operation have already been shown for alloys [21] and mono-phase NiAl [18,22,23] as well as Ni 3 Al [24,25] systems.…”
Section: Introductionmentioning
confidence: 99%
“…The mixing process was conducted in a N 2 atmosphere with the rotational speed of 200 rpm and the time of mixing was 4 h. Ball-to-powder ratio (BPR) was approximately 5:1. Presented mixing conditions were selected after the preliminary tests described in papers [16,17]. The morphology of the obtained powder mixtures is presented in Fig.…”
Section: Methodsmentioning
confidence: 99%